Multimodal Text-Powered Interactive E-Module for Enhancing English Structure Learning - Daud, Afrianto; Linda, Roza; Harfal, Zaldi; Nabila, Ovia; Suryani, Ade; Tahirah, Zahra (REiLA : Journal of Research and Innovation in Language, 2024)
This study aimed to develop an interactive e-module based on multimodal text for the Intermediate English Structure course in supporting digital learning at Universitas Riau, Indonesia. The research followed a systematic Research and Development (R&D) approach and applied the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, which integrated the initial research techniques with final evaluation methods to ensure the effectiveness of the e-module. This study utilized purposive sampling techniques which involved 42 students and experts in media and materials. The development started with a thorough analysis of students’ needs, obtaining a score of 3.05 which indicated high necessity. The subsequent step involved designing the desired product, which is an interactive e-module containing multimodal texts, that is, various types of texts which include written texts, images, animated videos and interactive quizzes. The e-module consists of six units; each containing sections such as video-based explanation, text-based descriptions, illustrative examples, interactive quizzes, and chapter summaries. Validation of the e-module was carried out by material and media experts, resulting in scores of 3.73 (indicating very valid) and 3.77 (indicating very valid) respectively. Then, when tested to students, the results revealed a 'clarity of language use in the learning material' indicator is 3.57 (indicating very good), while the 'ease of use' indicator stands at 3.60 (indicating very good). Thus, these results suggest that the developed e-module exhibits excellent quality and is well-suited to serve as a digital learning resource for the Intermediate Structure course in the English department at Universitas Riau, Indonesia. Furthermore, this e-module also has the potential to transform how students learn. With combination of different types of content, the researchers have created a tool that can set a new standard for digital learning at Universitas Riau and beyond.